"SILICON FROM SAND" – STAGE OF DEVELOPMENT OF SEMICONDUCTOR SILICON TECHNOLOGY: EXPERIENCE AND PROSPECTS - Kritska, Tetiana; Bazhenov, Yevhenii Vasylovych (Scientific Journal "Metallurgy", 2024)
On the basis of the analysis of modern methods of obtaining semiconductor silicon, critical factors affecting the prospects of the industry’s development are identified – these are the problems of raw material supply and the high energy intensity of production processes. As an alternative solution, a method of obtaining semiconductor-quality silicon directly from quartz sand is proposed, which excludes the use of expensive, scarce quartzites and charcoal. Ensuring the energy efficiency of the method is carried out due to the exclusion from the technology of the multi-tonnage, energy-intensive process of carbothermic reduction of quartzites in ore-thermal furnaces (stage of obtaining metallurgical silicon, temperature up to 2000°С, 12 17 MW∙g/t), exclusion from further technologies of methods of high-energy-consuming operations of distributive condensation of PGS (temperature below 60°C), explosive high-temperature hydrogen chloride synthesis process (temperature up to 2300°C), as well as operations of high-temperature hydrogenation of silicon tetrachloride (temperature 1270°C). The advantage of the new technology is also the possibility of disposal of man-made waste from the abrasive, electrode industry, organic silicon and other silicon-containing waste. Activation of the charge composition in the solid phase ensures its effective low-temperature chlorination in the mine chlorinator. Further stages of the technology are rectification purification of silicon tetrachloride, low-temperature hydrogenation to obtain silanes, gradual separation of PGS components (mixture of silanes, hydrogen chloride, hydrogen). The new technology provides the possibility of further production of polycrystalline silicon rods using the following methods: pyrolysis of monosilane (Dupon process), hydrogen reduction of silicon (CVD process), or granular silicon (pyrolysis of monosilane in a pseudo-liquefied layer of silicon particles – Dassel process). The use of low-energy-intensive processes for the production and purification of silanes, the utilization and reversal of intermediate technological products in the new technology opens up the possibility of variable use of known technologies in relation to the current demands of consumers for the quality of polycrystalline silicon.